Engineering technology, engineering education and engineering management proceedings of the 2014 International Conference on Engineering Technology, Engineering Education and Engineering Management (ETEEEM 2014), , Guangzhou, China, 15-16 November 2014 - Tan, Deyao (CRC Press, Taylor & Francis Group, 2015)
This volume contains papers presented at the International Conference on Engineering Technologies, Engineering Education and Engineering Management (ETEEEM 2014, Hong Kong, 15-16 November 2014). The book will be of interest to academics and professionals in Engineering Technologies, Engineering Education and Engineering Management.